2003
DOI: 10.2134/jeq2003.1887
|View full text |Cite
|
Sign up to set email alerts
|

Bedding and Seasonal Effects on Chemical and Bacterial Properties of Feedlot Cattle Manure

Abstract: Nutrients, soluble salts, and pathogenic bacteria in feedlot-pen manure have the potential to cause pollution of the environment. A three-year study (1998-2000) was conducted at a beef cattle (Bos taurus) feedlot in southern Alberta, Canada to determine the effect of bedding material [barley (Hordeum vulgare L.) straw versus wood chips] and season on the chemical and bacterial properties of pen-floor manure. Manure was sampled for chemical content (N, P, soluble salts, electrical conductivity, and pH) and popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 26 publications
9
62
1
Order By: Relevance
“…Details of the feedlot, pen manure and bedding material (Miller et al 2003), and details of the composting process (Miller et al 2005) have previously been reported. The inorganic fertilizer treatment consisted of 100 kg N ha…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the feedlot, pen manure and bedding material (Miller et al 2003), and details of the composting process (Miller et al 2005) have previously been reported. The inorganic fertilizer treatment consisted of 100 kg N ha…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…The barley was irrigated with a side-roll system. The extraction procedures and chemical analyses of the amendments applied have previously been reported (Miller et al 2003).…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…These workers considered that the retention of N may have been due to adsorption and/or immobilisation of N and sulphur by the C-rich bark. Miller et al (2003) reported that although the addition of sawdust or wood chips to cattle manure did not result in a reduction in faecal bacteria, this was almost certainly due to having too low a ratio of bedding material to manure.…”
Section: Introductionmentioning
confidence: 99%